Development of an Inquiry-Based Learning Model E-Module Assisted by the Heyzine Application on Students’ Mathematical Communication Skills - Miranda, Firdatul; Fajriana; Sinaga, Nurul Afni (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to develop an e-module based on inquiry-based learning model assisted by the heyzine application for students’ mathematical communication skills on data centralization and data dissemination materials at SMP Negeri 3 Lhokseumawe. The background of this study is the low mathematical communication skills of students, the teaching and learning process still uses books and teaching modules that tend to be boring for student and many teachers are still unfamiliar with the use of applications such as heyzine. The method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Product validation is carried out by media experts and material experts to determine the level of validity. Practicality and effectiveness are assessed through student response questionnaires and learning outcomes. The results showed that the validation of media experts obtained a score of 98.09%, and material experts 95.4% with the category of "very feasible." The practicality test of student responses reached 92.6% with the criteria of "very practical" and student learning outcomes reached an effectiveness level of 85% with the criteria of "very effective". These results indicate that the developed e-module is valid, practical, and effective for use in mathematics learning, especially in statistics material for grade VIII. This product is expected to support enjoyable learning and be relevant to students’ daily lives.